Implementation of computer optimization for design of electron guns - Ives, R.L.; Thuc Bui; Attarian, A.; Davis, S.; Gadson, S.; Tallis, W.; Hien Tran; Read, M.; Posth, M. (2008 33rd International Conference on Infrared, Millimeter and Terahertz Waves, 2008)
Computer optimization can dramatically reduce the time and cost to design electron beam devices. It also allows design of complex, 3D devices that would be impractical with manual design. Recent implementation of a magnetic solver into a 3D finite element electron beam trajectory code is allowing optimized design of the electrostatic, optical and magnetic configuration of 3D device. The process and examples will be presented.